Digital Flashcard Sebagai Media Pembelajaran Anatomi Fisiologi Kelas X - Nazwa Qintara; Nurul Hidayah; Titin Supiani (Journal on Education, 2025)
This study aims to develop learning media in the form of digital flashcards based on Quizlet, which are feasible and practical to use for Anatomy and Physiology subjects for class X students of the Beauty and Spa vocational program at SMK Negeri 1 Kemang.The research method employed is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results of the study indicated that the developed digital flashcards were deemed highly practical, with a score of 92% in the one-to-one trial, 89.2% in the small group, and 91.52% in the large group test. Consequently, this Quizlet-based digital flashcard media is deemed feasible and practical as a learning media, with the potential to enhance students' comprehension and memorization of Anatomy Physiology terms in an interactive manner.